Overlap of membranous nephropathy and IgA nephropathy in a patient with Kimura’s disease: a case report and literature review - Barbosa, Géssica Sabrine Braga; Neves, Precil Diego Miranda de Menezes; Mohrbacher, Sara; Abdo, André Néder Ramires; Cavalcante, Lívia Barreira; Menezes, Yara de; Sato, Victor Augusto Hamamoto; Oliveira, Érico de Souza; Pereira, Leonardo Victor Barbosa; Bales, Alessandra Martins; Frediani, Marcella Martins; Chocair, Pedro Renato; et al. (Frontiers in Immunology, 2024)
Introduction Kimura’s disease (KD) is a rare chronic inflammatory disorder characterized by subcutaneous lymphoid hyperplasia with peripheral eosinophilia. Kidney involvement is reported in 15%–18% of adult patients with KD, in many cases as nephrotic syndrome. We present a case of overlapping membranous nephropathy and IgA nephropathy associated with KD. Case report A 27-year-old man was admitted with a history of bilateral leg edema for the last 2 months and concomitant progressive increase of cervical mass and fever. Laboratory findings were as follows: peripheral leukocyte count, 10,080/mm³; eosinophils, 3,200/mm³ (31.7%); serum creatinine, 0.83 mg/dL; and eGFR: 140 mL/min per 1.73 m2. Urinalysis revealed the presence of hematuria and proteinuria and the following results: 24-h proteinuria, 12.9 g; serum albumin, 1.3 g/dL; and elevated IgE level, 750 kU/L. Serologies for hepatitis B, hepatitis C, HIV, and VDRL were all negative. Complement C3 and C4 levels were normal. No monoclonal protein was detected in blood and urine. Parasite infestation was discarded. A biopsy of the cervical lymph node revealed eosinophilic lymphoid hyperplasia, suggesting KD. A kidney biopsy revealed findings consistent with the overlapping of membranous nephropathy with IgA nephropathy. The patient was treated for KD with prednisone 1 mg/kg/d with progressive dose tapering and posterior association of methotrexate 15 mg/week. A renin–angiotensin system inhibitor was prescribed for nephrotic syndrome. The cervical mass regressed, and proteinuria achieved partial remission, with an increase in serum albumin level and normalization of eosinophils and IgE levels. Conclusion Although uncommon, kidney involvement must be considered in patients with KD. Glomerular diseases are the most frequent form of kidney injury.